Control of Positive and Negative Magnetoresistance in Iron Oxide-Iron Nanocomposite Thin Films for Tunable Magnetoelectric Nanodevices - Nichterwitz, Martin; Honnali, Shashank; Zehner, Jonas; Schneider, Sebastian; Pohl, Darius; Schiemenz, Sandra; Goennenwein, Sebastian T. B.; Nielsch, Kornelius; Leistner, Karin (ACS Applied Electronic Materials, 2020)
The perspective of energy-efficient and tunable functional magnetic nanostructures has triggered research efforts in the fields of voltage control of magnetism and spintronics. We investigate the magnetotransport properties of nanocomposite iron oxide/iron thin films with a nominal iron thickness of 5-50 nm and find a positive magnetoresistance at small thicknesses. The highest magnetoresistance was found for 30 nm Fe with +1.1% at 3 T. This anomalous behavior is attributed to the presence of Fe3O4-Fe nanocomposite regions due to grain boundary oxidation. At the Fe3O4/Fe interfaces, spin-polarized electrons in the magnetite can be scattered and reoriented. A crossover to negative magnetoresistance (-0.11%) is achieved at a larger thickness (>40 nm) when interface scattering effects become negligible as more current flows through the iron layer. Electrolytic gating of this system induces voltage-triggered redox reactions in the Fe3O4 regions and thereby enables voltage-tuning of the magnetoresistance with the locally oxidized regions as the active tuning elements. In the low-magnetic-field region (<1 T), a crossover from positive to negative magnetoresistance is achieved by a voltage change of only 1.72 V. At 3 T, a relative change of magnetoresistance about -45% during reduction was achieved for the 30 nm Fe sample. The present low-voltage approach signifies a step forward to practical and tunable room-temperature magnetoresistance-based nanodevices, which can boost the development of nanoscale and energy-efficient magnetic field sensors with high sensitivity, magnetic memories, and magnetoelectric devices in general.
CRIS-Team Scopus Importer:2022-04-14
Keywords: iron films; magnetite; magneto-ionic control; magnetoresistance; voltage control of magnetism